Model of Readiness and Success in Adopting Government Mobile (mGov) among Government Institutions in Indonesia - Muhammad Syarif, Hartawan; Ali, Rahman; Hoga, Saragih; Aedah, Abd Rahman (2021)
The concept of cellular government presents information that is oriented towards improving the quality of public services and organizations that use efficient and effective cellular services. This study discusses the preparation and successful adoption of cellular government mobile (mGov) among government institutions in Indonesia. This study provides knowledge and alternatives for implementing mobile adoption with mGov modeling that can be applied in determining readiness and success in adopting mobile applications. The researcher developed a research model using descriptive analytical methods by supporting, evaluating and adapting the model of readiness and success (ISRS), the technology readiness model (TRI), the successful model of construction IS from DeLone & McLead, the theory Information System (IS) use and security. In this study the models to be developed in this structure are 11 variables and 52 indicators. Path influence between variables is presented by 25 relationships. This study obtained an assessment of the implementation strategy, analysis of the readiness assessment model and adoption model that is appropriate for the development of government mobile applications among Indonesian government institutions.